2013
DOI: 10.2298/pif1304255m
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of different insecticides in controlling pollen beetle (Meligetes aeneus F.) in rapeseed crop

Abstract: SuMMARYSince pollen beetle, M. aeneus, is usually controlled by insecticides, the efficacy of several compounds with different modes of action against adult beetles was studied in a threeyear field study. The selected insecticides were: three pyrethroids (lambda-cyhalothrin, alpha-cypermethrin and bifenthrin), an oganophosphate (pirimiphos-methyl), a combination of an organophosphate and a pyrethroid (chlorpyrifos + cypermethrin) and a neonicotinoid (thiacloprid). The insecticides were applied at label rates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(18 reference statements)
0
1
0
Order By: Relevance
“… Todorov et al (2022) provide a list of parasitoid species found in oilseed rape fields in Bulgaria with comments on perspectives for biological control, but only for the family Pteromalidae . Oilseed rape pests, on the other hand, are relatively well studied in Serbian fields from both taxonomical and traditional chemical management aspects ( Kereši et al 2007 , Sekulić and Kereši 2007 , Štrbac et al 2007 , Mitrović et al 2008 , Milovac et al 2010 , Graora et al 2013 , Milovanović et al 2013 , Graora et al 2015 , Sivčev et al 2015 , Sivčev et al 2016 , Milovac 2016 , Marjanović and Prodanović 2021 ). Similarly, the parasitoid wasp fauna of other crops in Serbia, especially cereals and alfalfa, has also been well studied ( Tomanović et al 2003 , Kavallieratos et al 2004 , Kavallieratos et al 2005a , Kavallieratos et al 2005b , Tomanović et al 2008 , Žikić et al 2012 , Tomanović et al 2021 ), but currently, there is a gap in knowledge of the parasitoid wasp fauna in oilseed rape.…”
Section: Introductionmentioning
confidence: 99%
“… Todorov et al (2022) provide a list of parasitoid species found in oilseed rape fields in Bulgaria with comments on perspectives for biological control, but only for the family Pteromalidae . Oilseed rape pests, on the other hand, are relatively well studied in Serbian fields from both taxonomical and traditional chemical management aspects ( Kereši et al 2007 , Sekulić and Kereši 2007 , Štrbac et al 2007 , Mitrović et al 2008 , Milovac et al 2010 , Graora et al 2013 , Milovanović et al 2013 , Graora et al 2015 , Sivčev et al 2015 , Sivčev et al 2016 , Milovac 2016 , Marjanović and Prodanović 2021 ). Similarly, the parasitoid wasp fauna of other crops in Serbia, especially cereals and alfalfa, has also been well studied ( Tomanović et al 2003 , Kavallieratos et al 2004 , Kavallieratos et al 2005a , Kavallieratos et al 2005b , Tomanović et al 2008 , Žikić et al 2012 , Tomanović et al 2021 ), but currently, there is a gap in knowledge of the parasitoid wasp fauna in oilseed rape.…”
Section: Introductionmentioning
confidence: 99%